Pengaruh Teknik Komunikasi Persuasif Ikrama terhadap Kesadaran Religiusitas Masyarakat Kecamatan Cileunyi Kabupaten Bandung - Nazhiifah; Khuza'i, Rodliyah; Siddiq, Asep Ahmad (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Youth mosque is a separate community in the mosque. Likewise, the youth of the mosque, should be able to be an example for the surrounding community. The purpose of this study was to determine whether there was an influence between the program of activities and the study material provided by Ikrama on the religious attitude or religiosity of the community. The type of research used is descriptive quantitative. With a sample of 33 using a Likert scale from the number of 50 congregations. Data collection techniques through observation, distributing questionnaires, documentation, and interviews. Researchers used data analysis techniques in the form of validity, reliability, normality, simple regression, f-test, and the coefficient of determination. The theory used by the author to answer the research problem is Wiryanto's influence theory, Carl Hovland's persuasive communication theory, and Glock and Stark's theory of religiosity. From the results of the study, it was found that 21.5% had an influence on the program of activities and study materials provided by Ikrama with the religious attitude or religiosity of the community. Abstrak. Remaja masjid merupakan merupakan suatu komunitas tersendiri di dalam masjid. Begitupula remaja masjid, sudah seharusnya mampu menjadi contoh bagi masyarakat sekitar. Tujuan penelitian ini adalah guna mengetahui apakah terdapat pengaruh antara program kegiatan dan materi kajian yang diberikan oleh Ikrama terhadap sikap keberagamaan atau religiusitas masyarakat. Jenis penelitian yang digunakan adalah kuantitatif deskriptif. Dengan sampel 33 dengan menggunakan skala likert dari jumlah 50 jama’ah. Teknik pengumpulan data melalui observasi, penyebaran kuesioner, dokumentasi, dan wawancara. Peneliti menggunakan teknik analisa data berupa uji validitas, reliabelitas, normalitas, regresi sederhana, uji f, serta koefisien determinasi. Teori yang digunakan oleh penulis guna menjawab permasalahan penelitian yakni teori pengaruh dari Wiryanto, teori komunikasi persuasif dari Carl Hovland, dan Teori Religiusitas dari Glock dan Stark. Dari hasil penelitian, ditemukan sebesar 21,5% adanya pengaruh terhadap program kegiatan dan materi kajian yang diberikan oleh Ikrama dengan sikap keberagamaan atau religiusitas masyarakat.